The Effectiveness of Mnemonic Device Techniques in Improving Long-Term Memory in Learning in Elementary Schools: A Literature Review - Delima Tuesday Siagian; Nining Maida; Dede Margo Irianto; Rendi Restiana Sukardi (Equator Science Journal, 2023)
In a variety of disciplines taught in elementary schools, which frequently need substantial memorizing, the use of mnemonic device techniques has shown to be helpful in facilitating learning and strengthening long-term memory. This study intends to investigate how well various mnemonic device techniques and their theoretical foundations work to improve long-term memory. A literature review methodology was used to create the accumulated findings by analyzing pertinent study results, journal articles, and literature reviews that covered the studied designs. The results of this study show that mnemonic device strategies can help primary school pupils improve their long-term memory. A variety of techniques are included in the mnemonic device techniques, including (1) rhyme, (2) abbreviations, (3) peg word system, (4) loci method, and (5) keyword system. Students can maximize their brains' encoding and retrieval processes, which will boost memory retention, by using the proper mnemonic strategy during the learning process. This helps students remember and retain the information they have learnt. In conclusion, using mnemonic device approaches in primary school instruction can greatly aid pupils in developing long-term memory. As they provide useful tools to aid the learning process and improve students' memory of crucial knowledge, educators and practitioners are encouraged to incorporate these strategies into their teaching practices. The use of mnemonic techniques by students can help them overcome the difficulties associated with memorization and improve their overall learning outcomes.